Effects of a dietary intervention with conjugated linoleic acid on immunological and metabolic parameters in children and adolescents with allergic asthma – a placebo-controlled pilot trial. Issue 1 (December 2016) - Jaudszus, Anke; Mainz, Jochen; Pittag, Sylvia; Dornaus, Sabine; Dopfer, Christian; Roth, Alexander; Jahreis, Gerhard
Abstract Background Circumstantial evidence suggests that conjugated linoleic acid (CLA) beneficially modulates immune function in allergic subjects.C 9, t 11-CLA, naturally occurring in ruminant fats, is suggested to be the effective isomer. In contrast, for thet 10, c 12-CLA isomer, which is naturally found only in traces but usually constitutes a relevant part in commercial CLA mixtures, adverse effects have been reported. Aim of this study was to assess putative immunomodulatory effects of highly enrichedc 9, t 11-CLA in allergic subjects. To our best knowledge, our study is the first in that a CLA preparation was used for such purpose which was free oft 10, c 12-CLA. Design Twenty-nine asthmatic children and adolescents (age 6–18 y) with diagnosed allergic sensitization against grass pollen, house dust mite, or cat hair/epithelia consumed daily a portion of yoghurt containing either 3 g CLA (75 %c 9, t 11-CLA, 87 % purity) or placebo (safflower oil) over a period of 12 weeks. At study start and end, lung function parameters, specific IgE, in vitro allergen-induced cytokine production in peripheral blood mononuclear cells (PBMC), plasma ECP, urinary 8-oxodG as marker of oxidation, fatty acid profiles of erythrocytes, and routine haematological parameters were determined. Prior to blood samplings, 3-days dietary records were requested. Throughout the study, the participants documented daily their peak expiratory flow and kept protocol about their allergy symptoms and usage of demand medication. Results In contrast to the CLA group, PBMC-produced IFN-γ and IL-4 increased significantly and by trend, respectively, in the placebo group. Moreover, plasma ECP tended to increase in the placebo group. In the pollen subgroup, FEV1 improved upon both CLA and placebo oil supplementation. In both intervention groups, then -6/n -3 PUFA ratio in red blood cells decreased, mainly due to an increase inn -3 PUFA. Moreover, 8-oxodG excretion increased in both groups. No changes occurred regarding specific IgE concentrations, allergy symptoms, and volume parameters. Conclusion Our results indicate that CLA modestly dampens the inflammatory response on the cellular level. A clinically relevant amelioration of the symptoms could not be proved in atopic manifest patients. Trial registration NCT01026506.